First principle study of half metallic ferromagnetism and transport properties of spinel's ZnFe2(S/Se)4 for spintronic. (16th September 2021) - AlObaid, Abeer A; I Al-Muhimeed, Tahani; Rahim, Abdur; Nazir, Ghazanfar; Bouzgarrou, S; Mera, Abeer; Aljameel, A I; Hegazy, H H; Murtaza, G; Mahmood, Qasim
Abstract: Half metallic ferromagnetism received remarkable attention due to its immense technological applications in spintronic. In this perspective, thiospinels ZnFe2 S/Se4 is addressed by employing density functional theory (DFT) for spintronics and thermoelectric devices. The optimized energy versus volume leads to the confirmation of the Ferromagnetic (FM) states stability of both spinels. The formation energy confirms the thermodynamic stability. TDOS and PDOS are determined to confirm spin polarization and half-metallic ferromagnetism. Ferromagnetism is explored by exchange energies and magnetic moments. In addition, thermoelectric characteristics are explored by electrical and thermal conductivities, Seebeck coefficient, and power factor to evaluate their potential in thermoelectric applications.